The Influence of Auditor Characteristics on Audit Report Lag in Property and Real Estate Sector Companies - Azzahra, Nisrina; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
This study aims to determine the influence of Auditor Industry Specialization, Auditor Reputation, Auditor Gender, Auditor Education Level and Company Operation Complexity on Audit Report Lag with the Property and Real Estate Sector listed on the Indonesia Stock Exchange (IDX) for the period 2021 - 2023 as the population of the research object. Sampling was done using the purposive sampling technique, which was obtained by 14 companies so that the number of samples used was 42 observation data. The data analysis used in this study was using SPSS 27. The results of this study show that the variables of Auditor Industry Specialization, Auditor Reputation, Auditor Gender, and Auditor Education Level have no effect on Audit Report Lag. Meanwhile, the complexity of the Company’s operations has a positive effect on Audit Report Lag.